Analisis Potensi Kecurangan dalam Pengelolaan Dana Desa Menggunakan Fraud Triangle Theory: Studi Empiris di Desa Lokomea Kecamatan Biboki Utara Kabupaten Timor Tengah Utara - Vanesa Yosepha Empol; Anthon Simon Y. Kerihi; Minarni A. Dethan (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study is to explain the potential for fraud in the management of village funds using the Fraud Triangle Theory in Lokomea Village, North Biboki District, North Central Timor Regency. The research method used is qualitative descriptive. The results of this study show that the potential for fraud in village financial management in Lokomea Village can be analyzed through the Fraud Triangle Theory, which includes three main elements: 1. Pressure: Occurs when village fund managers face personal financial problems, community demands, or high development expectations, which can encourage misuse of funds. 2. Opportunity: Arises when the internal supervision and control system is weak, giving room for fund managers to abuse the budget undetected. 3. Rationalization: The fund manager tries to justify his actions, by considering budget deviations for projects or urgent needs as natural, even if it is contrary to the principles of transparency and accountability. To prevent fraud, strategic steps are needed such as increasing accountability, transparency, and ethics, involving the public in planning and oversight, and ensuring clear reporting and auditing. Thus, village financial management can be more accountable and effective.